Rancang Bangun Sistem Informasi Info Rapid Test Antigen di Jakarta Berbasis Website - Reza Phahlevi Junior; Agung Triayudi; Sari Ningsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The COVID-19 outbreak has reached the entire world, including Indonesia. With a pandemic like this, traveling out of town will experience difficulties because the government has issued a policy for the public to carry out a Rapid Test Antigen so that they can travel outside the city, and in the midst of a pandemic like this, all hospitals do not necessarily provide a Rapid Test Antigen. In this study, the authors created a website that contains information on hospitals that provide Rapid Test Antigen in Jakarta with the SDLC (System Development Life Cycle) method. The are used for this research is the entire DKI Jakarta area. The study uses data collection techniques by surveying directly to a hospital that provides the Rapid Test Antigen and secondary data obtained from the internet media. This application is expected to make it easier for residents of DKI Jakarta and those from outside the city to find out the location that provides the Rapid Antigen Test in Jakarta.